2014
DOI: 10.1128/genomea.01180-14
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Coxiella burnetii Strain Cb196, an Agent of Endocarditis in Saudi Arabia

Abstract: Coxiella burnetii Cb196, with a 2,006,415-bp genome, is a strain isolated from a 45-year-old man in Saudi Arabia with endocarditis. It belongs to the genotype MST51, which was detected for the first time only in this country. Cb196 shows more similarity to C. burnetii CbuK_Q154, belonging to genotype 8, which was phylogenetically close to MST51.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In both papers, MLVA genotyping revealed further discrimination of the MST types in two or three other subtypes [14,15]. The observation of region-specific genotypes is reported in the literature [16,[18][19][20], and the presence of novel genotypes in Brazil and Argentina reinforces this cartographic feature of the genetic diversity based on MST typing of Q fever.…”
Section: Discussionmentioning
confidence: 75%
“…In both papers, MLVA genotyping revealed further discrimination of the MST types in two or three other subtypes [14,15]. The observation of region-specific genotypes is reported in the literature [16,[18][19][20], and the presence of novel genotypes in Brazil and Argentina reinforces this cartographic feature of the genetic diversity based on MST typing of Q fever.…”
Section: Discussionmentioning
confidence: 75%
“…Since 2003, six new whole genomes of C. burnetii have become available in GenBank (142)(143)(144). Sixteen incomplete genomes can also be found (27,47,(145)(146)(147)(148)(149)(150). In 2009, Beare et al performed a comparative genomic analysis of four strains and found a total of 125 pseudogenes, of which 65 were highly conserved, and 8 IS families (142).…”
Section: Comparative Genomics and Pangenomic Analysismentioning
confidence: 99%
“…In Asia, limited studies on the C. burnetii genotype have been performed. The MST51 genotype was reported in Saudi Arabia in an endocarditis patient [ 29 ]. In Asia, as elsewhere in the world, more genotypic studies are needed to determine the geographical distribution of C. burnetii genotypes among humans and livestock infections.…”
Section: Discussionmentioning
confidence: 99%